Computational methods in photochemistry (CRC Press, 2005)
A concentrated source for the most recent computational methods as applied to organic photochemistry, this guide contains a historical perspective on the development of early semi-quantitative and quantitative methods in organic photochemistry. Written by one of the founders of modern theoretical and experimental photochemistry, it provides the most up-to-date summary of SOC computations for various organic diradicals and triplet species with listings of all the actual computed values, key concepts and computational methods designed to describe adiabatic and non-adiabatic behavior of excited species, and a vast dataset of experimental and computational results pertaining to nitrenes, including various alkyl-, vinyl-, aryl- and acylnitrenes.